2014
DOI: 10.1111/ggi.12220
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, reversibility, risk factors and the protective effect of high body mass index against sarcopenia in community‐dwelling older Chinese adults

Abstract: Aim:We examined the incidence and the reversibility of sarcopenia and their associated factors over a 4-year period using the European Working Group on Sarcopenia in Older People (EWGSOP) criteria. Methods:A total of 4000 community-dwelling older adults aged ≥65 years were evaluated for which detailed information regarding demographics, socioeconomic, medical history, lifestyle, and clinical factors were documented at baseline, 2 years, and 4 years later. Sarcopenia was defined according to the EWGSOP algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
149
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(176 citation statements)
references
References 59 publications
25
149
1
1
Order By: Relevance
“…Moreover a recent 4-year follow-up study on Chinese elderly people confirmed that the accomplishment of sarcopenia reversibility is associated with several lifestylerelated factors. In particular a high BMI resulted protective against sarcopenia occurrence; however, the increment of physical activity and the maintenance of a healthy weight was beneficial in the prevention of sarcopenia as well [72]. Further studies in different populations and with a longer follow-up are necessary to better investigate to what extent lifestyle behaviours might contribute to sarcopenia reversibility.…”
Section: Aging Skeletal Musclementioning
confidence: 97%
“…Moreover a recent 4-year follow-up study on Chinese elderly people confirmed that the accomplishment of sarcopenia reversibility is associated with several lifestylerelated factors. In particular a high BMI resulted protective against sarcopenia occurrence; however, the increment of physical activity and the maintenance of a healthy weight was beneficial in the prevention of sarcopenia as well [72]. Further studies in different populations and with a longer follow-up are necessary to better investigate to what extent lifestyle behaviours might contribute to sarcopenia reversibility.…”
Section: Aging Skeletal Musclementioning
confidence: 97%
“…46,47 Lifestyle behaviors such as physical inactivity, smoking, and poor diet are also important risk factors of sarcopenia. [48][49][50][51] Genetic factors also play a role in the etiology of sarcopenia. [52][53][54] Similar to osteopenia that predicts risk of fracture, sarcopenia is a predictor of falls, 55 fracture, 56 disability, [57][58][59] and mortality, 26,60 Sarcopenia also plays a predominant role in the development of frailty, 61 which is predictive of adverse events such as hospitalization, morbidity, disability, and mortality.…”
Section: The Prevalence Risk Factors and Consequences Of Sarcopeniamentioning
confidence: 99%
“…There is evidence suggesting that individuals who have knowledge of sarcopenia or a low value of muscle mass/strength were associated with fear of falls; their perception of health may be altered due to concerns that their conditions may predispose them to fracture, 56,98 which impact negatively upon quality of life. 97,99 Furthermore, those with sarcopenia were more likely to report having chronic diseases such as chronic obstructive pulmonary disease, stroke, and chronic kidney disease, 51,92,100 which have been associated with poor quality of life. 101,102 As mentioned earlier, sarcopenia and obesity often coexist and that a loss of muscle mass could be related to impaired metabolism (such as insulin resistance and metabolic syndrome), 68,70 both of which may have negative effects on quality of life.…”
Section: Potential Links Between Sarcopenia and Reduced Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations